Produção de extrato enzimático proteolítico por Aspergillus Oryzae CCBP001 em reator instrumentado por fermentação semi-sólida - Freitas, Adriana Crispim de (2013)
Enzyme production by solid state fermentation (SSF) is influenced by several factors that affect crop growth and production of microbial metabolites. The study of factors such as aeration and moisture in the air becomes indispensable for this bioprocess optimization. In this context, the present study aimed to assess the protease production by Aspergillus oryzae CCBP001 by FSS bioreactor columns. The FSS for the production of protease using the filamentous fungus A. oryzae CCBP 001 occurred in dynamic and static conditions in order to observe the method with the highest production. Therefore, tested the agroindustrial waste: canola cake, sunflower cake, wheat bran, almond cashew film and cottonseed meal as substrate, observing the production profile for different water activity (Aw) obtained by initial adding different volumes of water for humidification. Protease production in reactor columns in the optimized conditions was compared to production in flasks for 10 days. Evaluated procedures to recover, identify, focus and store the enzyme extract produced. For the concentration of the enzyme extract produced a study was conducted in dry "spray dryer" and followed up the storage time of the dry extract for 90 days. From the results it was possible to select the canola cake as the substrate where it presented a production 33% higher than the other substrates tested. In the study of operating conditions in reactor columns was possible to evaluate the influence of air flow, air humidity and substrate moisture in protease production. The use of glucose, maltodextrin and carboxymethylcellulose as adjuvants proved to be efficient with regard to maintenance of protease activity during the drying process using a "spray dryer", where it was possible to obtain a dry product with low values of humidity and Aw important for the storage process of enzyme extract. Spray drying of the enzyme extract and concentrate stockpile allowed the enzyme.